2015
DOI: 10.1007/s10694-014-0455-9
|View full text |Cite
|
Sign up to set email alerts
|

Globules and Beads: What Do They Indicate About Small-Diameter Copper Conductors that Have Been Through a Fire?

Abstract: Many fire investigators believe the presence of a rounded mass of re-solidified copper at the end of a small-diameter copper conductor means the conductor was energized at the time of the fire. While testing performed in the course of fire investigations by others and in this work has demonstrated that beads of re-solidified copper may be present on conductors known to have voltage present at the time of the fire, there may also be globules of re-solidified copper on conductors known not to have been energized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 3 publications
0
4
0
13
Order By: Relevance
“…Apesar de não haver uma característica definitiva para a diferenciação, verifica-se que há uma tendência na literatura em reconhecer características distintivas entre fios energizados e não energizados, representadas por uma linha de demarcação devido às diferenças entre os cristais de cobre fundidos e aqueles mantidos a temperatura ambiente 2,5,6,9,13,14 . Para se chegar a uma conclusão pericial, essas características devem ser corroboradas com os demais elementos materiais do local dos fatos, exigindo o conhecimento da cena do incêndio e a aplicação do método científico.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Apesar de não haver uma característica definitiva para a diferenciação, verifica-se que há uma tendência na literatura em reconhecer características distintivas entre fios energizados e não energizados, representadas por uma linha de demarcação devido às diferenças entre os cristais de cobre fundidos e aqueles mantidos a temperatura ambiente 2,5,6,9,13,14 . Para se chegar a uma conclusão pericial, essas características devem ser corroboradas com os demais elementos materiais do local dos fatos, exigindo o conhecimento da cena do incêndio e a aplicação do método científico.…”
Section: Discussionunclassified
“…Alguns dos artigos 14 confirmaram a existência de um gradiente acentuado de temperatura nas pérolas criadas por falhas elétricas após o corte da seção transversal, indicando que o exame das microestruturas pode fornecer um método para identificar a causa, confirmando a aplicabilidade da metalografia.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…If continued for long periods of time, the conduction will be molten, and due to the released energy arc beads will be formed where the wires are melted. Analyzing the characteristics of arc beads at the fire scene will provide a reference for determining the cause of the fire [ 7 , 8 , 9 , 10 ]. Using optical microscopy (OM), Takak et al [ 11 ] produced metallographic photographs of short-circuit arc beads for the first time and found that the short-circuit microstructure of an arc bead was composed of fine cellular crystals.…”
Section: Introductionmentioning
confidence: 99%